A palladium-based high-efficiency catalyst and its preparation method and application
By controlling the raw material ratio and reaction process of palladium-based catalysts, uniform small-particle palladium nanoparticles are generated, which solves the problems of large particle size, uneven distribution and poor stability of the existing catalysts, and achieves efficient catalysis and good current collector performance .
Patent Information
- Application Number
- CN202211432793.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-11-16
AI Technical Summary
The existing palladium-based catalysts have large average particle size and uneven distribution, resulting in low catalytic efficiency, large usage, and poor placement stability, which is prone to agglomeration and precipitation, resulting in a decrease in catalytic efficiency.
By selecting and proportioning the raw materials and controlling the reaction process, palladium nanoparticles with the target particle size are generated. The average particle size of the palladium nanoparticles is small and uniform in distribution, and the placement stability is good at room temperature, and the efficiency of catalytic preparation of current collectors is high.
The preparation of palladium-based high-efficiency catalyst is achieved, with high catalytic efficiency, low usage, excellent stability and performance of the catalytic system, and excellent performance of the prepared current collector.
Smart Images

Figure CN115709289B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of palladium catalyst preparation, and in particular to a palladium high-efficiency catalyst and a preparation method and application thereof. Background Art
[0002] As the advantages of the emerging sandwich-structured flexible current collector become increasingly prominent, the industry is conducting more and more extensive research on the process of preparing the current collector with this structure. Among them, the chemical deposition method is used to prepare the negative electrode current collector, which is favored due to its low cost, high production efficiency, roll-to-roll and industrial production. The key to preparing a conductive film layer with good coating quality, good resistance uniformity and good adhesion by chemical deposition is an efficient catalytic system.
[0003] In the existing technical solutions, such as CN111446453A, it is usually necessary to treat the flexible substrate to be plated in a roughening and activation treatment solution before chemical copper plating. The purpose of roughening and activation is mainly to allow particles with catalytic properties to adsorb to the surface of the substrate. However, this method usually has the disadvantages of poor dispersion of catalyst cores, random dispersion or uneven dispersion, resulting in poor copper plating quality and poor adhesion of the obtained conductive film layer; or the time-dependent instability of the catalyst leads to defects or streaks in the coating, resulting in poor coating uniformity.
[0004] In order to better achieve the goal of enhancing the adhesion between the copper film and the substrate by applying an organic bonding layer of the same system as the substrate; it is necessary to regulate the catalyst formula and dosage to achieve the target penetration amount, so that the copper layer grows not only on the surface, but also starts from the inside of the organic bonding layer, thereby achieving better bonding strength.
[0005] However, the current palladium catalysts have large average particle size, uneven distribution, and small specific surface area, resulting in low catalytic efficiency and large usage amount. As the usage amount of the catalytic system increases, more catalysts are attached to the surface, resulting in catalyst waste. As the coating amount of the catalyst increases, the catalyst agglomerates, thereby affecting the quality of copper plating during current collector preparation.
[0006] In addition, due to poor storage stability, palladium-based catalysts need to be used quickly after preparation, otherwise they will easily agglomerate and produce precipitation after being left for a period of time, resulting in a significant decrease in their catalytic efficiency.
[0007] Based on the above situation, the present invention proposes a palladium-based high-efficiency catalyst for preparing a current collector and a preparation method and application thereof, which can effectively solve the above problems. Summary of the invention
[0008] The purpose of the present invention is to provide a palladium-based high-efficiency catalyst and its preparation method and application. The preparation method of the palladium-based high-efficiency catalyst of the present invention can generate palladium nanoparticles of target particle size through the selection and proportion configuration of raw materials and the control of the reaction process. The palladium nanoparticles in the mother liquor of the palladium-based high-efficiency catalyst with a particle size within the target range have a high content of palladium nanoparticles, a high degree of preparation reduction, and a high yield; the average particle size of the palladium nanoparticles is small and evenly distributed, both in the range of 2 to 8 nm; the palladium-based high-efficiency catalyst has good stability at room temperature; the palladium nanoparticles in the palladium-based high-efficiency catalyst have a large specific surface area, and the efficiency of catalytic preparation of the current collector is high and the effect is good (the prepared current collector has excellent performance).
[0009] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0010] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0011] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 3 to 10 parts by weight of a palladium salt and 5 to 32 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to a reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 1.5 to 6:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0012] After a large number of creative experiments, the inventors found that when the mass ratio of dispersant to (composite) palladium salt is less than 1.5:1, the synthesized palladium nanoparticles have large particle size, uneven distribution and poor stability; when the mass ratio of dispersant to palladium salt is greater than 6:1, the particle size and stability of the synthesized palladium nanoparticles do not change significantly, but the catalytic activity will be significantly reduced due to excessive dispersant, resulting in rough copper growth and difficulty in plating.
[0013] In addition, as the reaction proceeds, the content of palladium nanoparticles obtained by the reaction will become higher and higher. By adding a dispersant to coat and disperse the palladium nanoparticles, the dispersion stability of the palladium nanoparticles in the mother solution of the present invention can be effectively provided.
[0014] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0015] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 80% to 98%, and the weight percentage content of the fluorine-containing surfactant is 0.1% to 2%.
[0016] The preparation method of the palladium-based high-efficiency catalyst of the present invention can generate palladium nanoparticles with a target particle size by selecting and proportioning raw materials and controlling the reaction process. The palladium nanoparticle mother liquor of the palladium-based high-efficiency catalyst with a particle size within the target range has a high content of palladium nanoparticles, a high degree of preparation reduction, and a high yield.
[0017] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. The average particle size of palladium nanoparticles in the palladium-based high-efficiency catalyst within the target range is small and evenly distributed, all in the range of 2 to 8 nm.
[0018] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. Palladium-based high-efficiency catalysts with particle sizes within the target range have good stability at room temperature; and the larger the particle size, the earlier precipitation occurs.
[0019] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. The palladium nanoparticles with a particle size within the target range have a large specific surface area in the palladium-based high-efficiency catalyst, high efficiency in catalytic preparation of current collectors, and good effect (the prepared current collectors have excellent performance).
[0020] During the preparation process of the palladium nanoparticles, the stirring is uniform, and the stirring temperature is 40-50°C, the stirring speed is 400-800rpm, and the stirring time is 30-60min (so that the palladium salt can be fully dissolved and the problem of reduced conversion rate caused by incomplete dissolution of the palladium salt can be reduced). The reaction temperature during the reaction process is 95-125°C, the stirring speed is 400-800rpm, and the reaction time is 1.5-2.5h.
[0021] In the preparation method of the palladium-based high-efficiency catalyst of the present invention, the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol, and the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate, wherein the reducing solvent acts as a solvent and a reducing agent at the same time, and no additional reducing agent needs to be added, which reduces the reduction reaction rate and makes the synthesized nanoparticles (particles) smaller and more uniform;
[0022] However, when the existing reaction temperature is 50-80°C, the reaction system of the present invention will not react, that is, the palladium-based high-efficiency catalyst of the present invention cannot be prepared. After a large number of creative experiments, the inventors found that the reaction process is controlled as follows: "In the preparation process of the palladium nanoparticles, the stirring is uniform, and the stirring temperature is 40-50°C, the stirring speed is 400-800rpm, and the stirring time is 30-60min; the reaction temperature during the reaction is 95-125°C, the stirring speed is 400-800rpm, and the reaction time is 1.5-2.5h", that is, a reasonable reaction temperature range and an appropriate stirring rate, so that the reaction system of the present invention can react more slowly and at a more uniform rate to obtain smaller, more uniform, and larger specific surface area nanoparticles (particles).
[0023] In practical applications, the reducing solvent may be any one or more of ethyl lactate, tetraethylene glycol and triethylene glycol.
[0024] As a preferred solution, in step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol.
[0025] As a more preferred solution, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:25-35.
[0026] In the preparation method of the palladium-based high-efficiency catalyst of the present invention, the inventor has found through a large number of creative experiments that the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol in a certain proportion, the reducing property of ethyl lactate is stronger than that of triethylene glycol, and the two are used in a mass ratio of 100:25-35, which plays a good synergistic role, and cooperates with other components (a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate), combined with the control of the reaction process, so that the reaction system of the present invention can be kept in a slow and uniform reaction rate, and the nanoparticles (particles) obtained are smaller, more uniform, and have a larger specific surface area; it can effectively avoid the local occurrence of excessively fast reaction rates, and improve the continuous stability of the reduction reaction; it can also increase the boiling point of the mixed solvent, and further ensure the continuous stability of the reaction system.
[0027] In practical applications, the palladium salt may be at least one of ammonium chloropalladate, tetraamminepalladium nitrate, palladium nitrate, palladium acetate and palladium chloride.
[0028] As a preferred solution, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0029] As a more preferred solution, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.1-0.15.
[0030] In the preparation method of the palladium-based high-efficiency catalyst of the present invention, the inventors have found through a large number of creative experiments that after palladium acetate (slowly dissolving when used alone) and tetraammine palladium nitrate are dissolved in the reducing solvent, the tetraammine palladium nitrate can generate amino groups, consume hydrogen ions in the reaction system, improve the reaction activity of the reducing solvent, increase the content of palladium ions released by palladium acetate in the reaction system of the present invention, and increase the concentration of free palladium ions in the reaction system. The two are used in a mass ratio of 1:0.1 to 0.15, which plays a good synergistic role and can keep the palladium ion concentration in the reaction system constant within a certain range, thereby ensuring and cooperating with other components (the reducing solvent). Combined with the reaction process control, the reaction system of the present invention can be kept in a slow and uniform reaction rate to obtain smaller and more uniform nanoparticles (particles) with a larger specific surface area.
[0031] As a preferred solution, the dispersant is any one or more of Solsperse-3000, Solsperse-9000, Solsperse-24000, Solsperse-46000 and Solsperse-20000 of Lubrizol, USA.
[0032] As a more preferred solution, the dispersant is Solsperse-46000.
[0033] Compared with other dispersants, when the dispersant is Solsperse-46000, the molecular weight is relatively large, and the wrapping and protection effect on the synthesized nanoparticles is better, making the synthesized particles smaller, more stable, and less prone to agglomeration. However, too large a molecular weight will cause the outer surface of the synthesized particles to be too strongly wrapped, reducing the catalytic effect to a certain extent.
[0034] As a preferred embodiment, the fluorocarbon surfactant is any one or more of perfluoro terminal carboxylate, perfluoroalkyl ethanesulfonate, perfluorooctyl methyl sulfate, perfluoroalkyl ether phosphate, perfluoropolyether carboxylic acid, fluorinated alkylamine quaternary ammonium salt, fluorinated alkyl amido quaternary ammonium salt, fluoroalkyl ammonium salt, carboxy betaine, sulfonate betaine, sulfate betaine, fluoroalkyl polyoxyethylene ether alcohol, fluorinated alkyl sulfonamide alcohol, fluorinated alkyl benzene and fluorinated alkane.
[0035] The invention also provides a palladium-based high-efficiency catalyst, which is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0036] The invention also provides an application of the palladium-based high-efficiency catalyst in chemical copper plating.
[0037] The application of the palladium-based high-efficiency catalyst in chemical copper plating includes the following steps:
[0038] a. Organic bonding layer primer: a non-conductive resin is applied on the surface of the substrate by coating to form an organic bonding layer on the surface of the substrate;
[0039] b. Applying a catalyst layer: applying the palladium-based high-efficiency catalyst on the surface of the organic bonding layer by coating, and driving the nano-scale palladium nanoparticles into the organic bonding layer through the penetration of the solvent;
[0040] c. Chemical copper plating process: immersing in chemical copper plating solution to form a metal copper film and metal copper particles on the surface of the non-conductive resin adsorbing palladium nanoparticles and the penetration layer.
[0041] The non-conductive resin is a photo-induced reactive resin, a thermally induced reactive resin or a thermoplastic resin.
[0042] When the organic bonding layer is a photo-initiated reaction type resin, the organic bonding layer is subjected to an exposure treatment before the chemical copper plating process.
[0043] When the organic bonding layer is a photo-initiated reaction type resin, the organic bonding layer is subjected to an exposure treatment and a development treatment, and then a chemical copper plating process is performed to form a metal conductive copper film with a pattern.
[0044] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0045] The preparation method of the palladium-based high-efficiency catalyst of the present invention can generate palladium nanoparticles of target particle size through the selection and proportion configuration of raw materials and the control of the reaction process, and the preparation reduction degree is high and the yield is high (the reaction is complete, close to 100%). The palladium nanoparticle content in the mother liquor of the palladium-based high-efficiency catalyst with the particle size of the palladium nanoparticles within the target range is high;
[0046] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. The average particle size of palladium nanoparticles in the palladium-based high-efficiency catalyst within the target range is small and evenly distributed, all in the range of 2 to 8 nm.
[0047] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. Palladium-based high-efficiency catalysts with a particle size within the target range have good stability when placed at room temperature.
[0048] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated, and the average particle size of the palladium nanoparticles is small and evenly distributed. The specific surface area of the palladium nanoparticles of the present invention is 180 m 2 / g-450m 2 / g, that is, the palladium nanoparticles in the palladium-based high-efficiency catalyst with a particle size within the mesh range have a large specific surface area, a high efficiency in catalytic preparation of the current collector, and a good effect (the prepared current collector has excellent performance). BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a graph showing the catalyst membrane surface quality test results after the palladium-based high-efficiency catalyst coating obtained in Example 5 of the present invention and Comparative Example 0 was applied.
[0050] Figure 2 The cross-sectional morphology of the copper film quality of the copper-plated samples of Example 5 and Comparative Example 6 of the present invention after copper plating is completed. DETAILED DESCRIPTION
[0051] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific examples, but it should not be understood as a limitation of this patent.
[0052] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0053] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0054] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 3 to 10 parts by weight of a palladium salt and 5 to 32 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to a reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 1.5 to 6:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0055] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0056] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 80% to 98%, and the weight percentage content of the fluorine-containing surfactant is 0.1% to 2%.
[0057] Preferably, during the preparation of the palladium nanoparticles, the stirring is uniform at a stirring temperature of 40 to 50°C, a stirring speed of 400 to 800 rpm, and a stirring time of 30 to 60 min; the reaction temperature during the reaction is 95 to 125°C, the stirring speed is 400 to 800 rpm, and the reaction time is 1.5 to 2.5 h.
[0058] Preferably, in step 1), the reducing solvent is a mixed complex solvent of ethyl lactate and triethylene glycol.
[0059] Preferably, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:25-35.
[0060] Preferably, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0061] Preferably, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.1-0.15.
[0062] Preferably, the dispersant is Solsperse-46000 from Lubrizol, USA.
[0063] The fluorocarbon surfactant is any one or more of perfluoro terminal carboxylates, perfluoroalkyl ethane sulfonates, perfluorooctyl methyl sulfates, perfluoroalkyl ether phosphates, perfluoropolyether carboxylates, fluorinated alkylamine quaternary ammonium salts, fluorinated alkyl amido quaternary ammonium salts, fluoroalkyl ammonium salts, carboxy betaine, sulfonate betaine, sulfate betaine, fluoroalkyl polyoxyethylene ether alcohol, fluorinated alkyl sulfonamide alcohol, fluorinated alkyl benzene and fluorinated alkane.
[0064] A palladium-based high-efficiency catalyst is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0065] An application of the palladium-based high-efficiency catalyst in chemical copper plating.
[0066] Embodiment 1:
[0067] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0068] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 3 parts by weight of a palladium salt and 18 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to the reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 6:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0069] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0070] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 80%, and the weight percentage content of the fluorine-containing surfactant is 0.1%.
[0071] In this embodiment, during the preparation of the palladium nanoparticles, the stirring was uniformly performed at a stirring temperature of 40°C, a stirring speed of 400 rpm, and a stirring time of 60 min; the reaction temperature during the reaction was 95°C, the stirring speed was 400 rpm, and the reaction time was 2.5 h.
[0072] In this embodiment, in step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol.
[0073] In this embodiment, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:25.
[0074] In this embodiment, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0075] In this embodiment, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.1.
[0076] In this embodiment, the dispersant is Solsperse-46000 produced by Lubrizol of the United States.
[0077] The fluorocarbon surfactant is a perfluorinated terminal carboxylate.
[0078] A palladium-based high-efficiency catalyst is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0079] Embodiment 2:
[0080] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0081] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 10 parts by weight of a palladium salt and 15 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to the reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 1.5:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0082] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0083] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 98%, and the weight percentage content of the fluorine-containing surfactant is 2%.
[0084] In this embodiment, during the preparation of the palladium nanoparticles, the stirring was uniformly performed at a stirring temperature of 50°C, a stirring speed of 800 rpm, and a stirring time of 30 min; the reaction temperature during the reaction was 125°C, a stirring speed of 800 rpm, and a reaction time of 1.5 h.
[0085] In this embodiment, in step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol.
[0086] In this embodiment, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:35.
[0087] In this embodiment, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0088] In this embodiment, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.15.
[0089] In this embodiment, the dispersant is Solsperse-46000 produced by Lubrizol of the United States.
[0090] The fluorocarbon surfactant is perfluoropolyether carboxylic acid.
[0091] A palladium-based high-efficiency catalyst is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0092] Embodiment 3:
[0093] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0094] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 5 parts by weight of a palladium salt and 25 parts by weight of a dispersant are weighed in parts by weight, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to the reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 5:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0095] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0096] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 85%, and the weight percentage content of the fluorine-containing surfactant is 0.8%.
[0097] In this embodiment, during the preparation of the palladium nanoparticles, the stirring is uniform with a stirring temperature of 42°C, a stirring speed of 500 rpm, and a stirring time of 50 min; the reaction temperature during the reaction is 105°C, the stirring speed is 500 rpm, and the reaction time is 2 h.
[0098] In this embodiment, in step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol.
[0099] In this embodiment, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:28.
[0100] In this embodiment, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0101] In this embodiment, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.12.
[0102] In this embodiment, the dispersant is Solsperse-46000 produced by Lubrizol of the United States.
[0103] The fluorocarbon surfactant is a perfluoro terminal carboxylate and a fluoroalkyl polyoxyethylene ether alcohol in a mass ratio of 1:1.
[0104] A palladium-based high-efficiency catalyst is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0105] Embodiment 4:
[0106] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0107] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 8 parts by weight of a palladium salt and 24 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to the reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 3:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0108] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0109] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 94%, and the weight percentage content of the fluorine-containing surfactant is 1.6%.
[0110] In this embodiment, during the preparation of the palladium nanoparticles, the stirring is uniform with a stirring temperature of 47°C, a stirring speed of 700 rpm, and a stirring time of 40 min; the reaction temperature during the reaction is 115°C, the stirring speed is 700 rpm, and the reaction time is 2 h.
[0111] In this embodiment, in step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol.
[0112] In this embodiment, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:32.
[0113] In this embodiment, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0114] In this embodiment, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.14.
[0115] In this embodiment, the dispersant is Solsperse-46000 produced by Lubrizol of the United States.
[0116] The fluorocarbon surfactant is fluoroalkyl polyoxyethylene ether alcohol.
[0117] A palladium-based high-efficiency catalyst is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0118] Embodiment 5:
[0119] A method for preparing a palladium-based high-efficiency catalyst comprises the following steps:
[0120] 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 6.5 parts by weight of a palladium salt and 26 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to the reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 4:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles;
[0121] 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst;
[0122] In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 90%, and the weight percentage content of the fluorine-containing surfactant is 0.12%.
[0123] In this embodiment, during the preparation of the palladium nanoparticles, the stirring is uniform with a stirring temperature of 45°C, a stirring speed of 600 rpm, and a stirring time of 40 min; the reaction temperature during the reaction is 110°C, the stirring speed is 600 rpm, and the reaction time is 2 h.
[0124] In this embodiment, in step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol.
[0125] In this embodiment, the mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:30.
[0126] In this embodiment, in step 1), the palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate.
[0127] In this embodiment, the mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.13.
[0128] In this embodiment, the dispersant is Solsperse-46000 produced by Lubrizol of the United States.
[0129] The fluorocarbon surfactant is a perfluorinated terminal carboxylate.
[0130] A palladium-based high-efficiency catalyst is prepared by adopting the preparation method of the palladium-based high-efficiency catalyst.
[0131] Comparative Example 0:
[0132] The difference from Example 5 is that in step 1), the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 1:1, and the rest is the same as Example 5.
[0133] Comparative Example 1:
[0134] The difference from Example 5 is that in step 1), the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 7:1, and the rest is the same as Example 5.
[0135] Comparative Example 2:
[0136] The difference from Example 5 is that during the preparation of the palladium nanoparticles, the reaction temperature is 80° C., and the rest is the same as Example 5.
[0137] Comparative Example 3:
[0138] The difference from Example 5 is that the reducing solvent is replaced by butyl acetate, and the rest is the same as Example 5.
[0139] Comparative Example 4:
[0140] The difference from Example 5 is that the reducing solvent is only ethyl lactate without triethylene glycol, and the rest is the same as Example 5.
[0141] Comparative Example 5:
[0142] The difference from Example 5 is that the palladium salt is palladium nitrate, and the rest is the same as Example 5.
[0143] Comparative Example 6:
[0144] The difference from Example 5 is that the palladium salt is palladium acetate and tetraammine palladium nitrate is absent. The rest is the same as Example 5.
[0145] Comparative Example 7:
[0146] The difference from Example 5 is that the dispersant is Solsperse-24000 produced by Lubrizol of the United States, and the rest is the same as Example 5.
[0147] The performance tests are performed on the preparation methods of the palladium-based high-efficiency catalysts obtained in Examples 1 to 5 of the present invention and Comparative Examples 0 to 7, and the common palladium-based catalysts (obtained by reducing by adding a reducing agent). The test results are shown in Table 1:
[0148] The test method for the reaction degree of the mother liquor is as follows: take 1 mL of the mother liquor into a test tube, add 5 mL of saturated NaCl solution, shake evenly, and filter using a 1 μm glass fiber filter to obtain the supernatant. Observe the color of the supernatant. If the reaction is complete, it is colorless and transparent. If it is yellow to orange, the palladium salt has not reacted completely.
[0149] Among them, the test method for the average particle size and particle size distribution of palladium nanoparticles is to dilute the catalyst 8 to 10 times with electronic grade ethyl lactate, prepare the sample using the transmission electron microscope TEM sample preparation method, take photos with the transmission electron microscope TEM and count the particle size of the palladium nanoparticles to calculate the average particle size of the palladium nanoparticles.
[0150] Time stability evaluation method: Take 30 mL of the prepared palladium-based high-efficiency catalyst into a transparent glass sample bottle, leave it for a week to observe whether there is precipitation at the bottom of the bottle, and filter it with a 1 μm glass fiber filter membrane to observe whether there are particles precipitated.
[0151] Table 1
[0152]
[0153]
[0154] Note: “-” in the above table means that the test has no statistical significance because no reaction product was obtained.
[0155] As can be seen from the above table, the preparation method of the palladium-based high-efficiency catalyst of the present invention has the following advantages: by selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated, and the reduction degree of the preparation is high, the yield is high (the reaction is complete, close to 100%), and the palladium nanoparticle content in the mother liquor of the palladium-based high-efficiency catalyst with a particle size within the target range is high;
[0156] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. The average particle size of palladium nanoparticles in the palladium-based high-efficiency catalyst within the target range is small and evenly distributed, all in the range of 2 to 8 nm.
[0157] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated. Palladium-based high-efficiency catalysts with a particle size within the target range have good stability when placed at room temperature.
[0158] By selecting and proportioning raw materials and controlling the reaction process, palladium nanoparticles of target particle size can be generated, and the average particle size of the palladium nanoparticles is small and evenly distributed. The specific surface area of the palladium nanoparticles of the present invention is 180 m 2 / g-450m 2 / g, that is, the palladium nanoparticles in the palladium-based high-efficiency catalyst with a particle size within the mesh range have a large specific surface area, a high efficiency in catalytic preparation of the current collector, and a good effect (the prepared current collector has excellent performance).
[0159] The invention also provides an application of the palladium-based high-efficiency catalyst in chemical copper plating.
[0160] Preparation method of negative current collector:
[0161] The above-prepared palladium-based high-efficiency catalyst (coating solution) Examples 1-5 and Comparative Examples 0-1, 4, and 6-7 were selected to prepare current collectors respectively.
[0162] First, an organic bonding layer is coated on the flexible substrate, which includes, by weight: 66.5 parts of ethyl lactate, 20.5 parts of Sarbox SB-400 and 10.5 parts of dipentaerythritol hexaacrylate (DPHA), 2 parts of 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 0.01 parts of p-hydroxyanisole (MEHQ), and 0.49 parts of BYK-333.
[0163] After baking at 80°C for 60 seconds, a 500 nm thick organic bonding layer was formed. The above-mentioned palladium-based high-efficiency catalyst was prepared at a rate of 3.1 g / m 2 The base film is exposed to a UV light with a wavelength of 304-324 nm for 10 seconds, and then placed in a copper plating solution at 37-39°C, wherein the copper plating solution comprises: 5 g / L copper sulfate, 10 g / L potassium sodium tartrate, 5 g / L disodium EDTA, 7 g / L sodium hydroxide, 7 g / L formaldehyde, 2.5 g / L methanol, 20 mg / L potassium ferrocyanide, and 15 mg / L 2,2′-bipyridine. The conductive copper layer is prepared after 384 seconds of copper plating.
[0164] The following tests are conducted on the quality of the palladium-based high-efficiency catalyst coating film, the quality of the copper film after copper plating, and its conductivity:
[0165] Among them, the quality assessment method of the palladium-based high-efficiency catalyst coating membrane surface is as follows: take the sample with the catalyst coating applied in the above-mentioned current collector preparation, and check the agglomeration of the catalyst applied on the membrane surface under a confocal microscope with a 50x lens.
[0166] Copper film quality assessment method:
[0167] Copper film density test: Take the copper-plated samples and use FEI helios 660 scanning electron microscope to test the cross-sectional morphology of the copper film and observe the density of the copper film.
[0168] Conductivity test: Take the prepared sample with a size greater than 10 x 10 cm and use a 4-probe square resistance meter to test the surface square resistance of 12 points on the surface of the sample and calculate its uniformity.
[0169] The samples coated with the palladium-based high-efficiency catalyst obtained in the above-mentioned Example 5 and Comparative Example 0 were respectively taken, and the quality of the catalyst coating membrane surface was evaluated according to the above-mentioned palladium-based high-efficiency catalyst coating membrane surface quality evaluation method, wherein the catalyst dosage in Example 5 was increased to 6.2 g / m 2 The sample of Example 5-2 was obtained and the quality of the catalyst membrane surface was also confirmed. The test results are as follows Figure 1 As shown, it can be seen that there is obvious agglomeration in the comparative example, while no obvious agglomeration is observed after the catalyst prepared by the method of the present application is formed into a film. The amount of catalyst used in Example 5-2 is doubled, and no agglomeration is observed on the film surface, indicating that the catalyst system of the present application has good dispersibility and stability, and good film-forming effect.
[0170] The copper-plated examples 1-5 and comparative examples 0-1, 4, 6-7 were taken respectively. According to the above method for evaluating the quality of the copper-plated copper film, the resistance uniformity of the samples was tested, and the test results are shown in Table 2 below:
[0171] Table 2
[0172]
[0173] It can be seen from the data in the above table that the metallic copper film prepared based on the catalyst formula provided by the present invention has good conductivity and uniformity. The ratio of the dispersant to the palladium salt in the catalyst preparation process of Comparative Example 0 and Comparative Example 1 relative to Example 5 exceeds the optimal ratio range of the present invention. When the ratio is small, the prepared catalyst particles are larger and the copper plating quality is relatively poor; when the ratio is large, although the prepared catalyst particles are smaller, the dispersion wrapped on the surface of the palladium nanoparticles is more, resulting in a significant decrease in the catalyst activity.
[0174] The average particle size, distribution range and dispersion stability of the catalyst particles obtained in Comparative Examples 4 and 6 are all inferior to those in Example 5, and the surface square resistance of the prepared current collector is relatively poorly uniform.
[0175] Comparative Example 7 selected a non-preferred dispersant provided in the present invention for preparation. The dispersion of the obtained catalyst particles was poorer than that of Example 5, but the particle size of the nanoparticles was also within a good range. The surface resistance of the prepared current collector was relatively poorly uniform.
[0176] The copper-plated samples of the above-mentioned Example 5 and Comparative Example 6 were taken respectively, and the side cross-sectional morphology of the samples was tested according to the above-mentioned method for evaluating the quality of the copper-plated copper film. The test results are as follows: Figure 2As shown, the copper film on the surface of the current collector prepared by the catalyst formula provided by the present invention has good density, while in Comparative Example 6, a palladium salt other than the preferred one of the present invention is used, and the palladium nanoparticles obtained are larger and the uniformity is also deteriorated. Therefore, the copper film prepared based on this catalyst has poor density and the surface resistance is correspondingly increased.
[0177] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a palladium-based high-efficiency catalyst, characterized in that: The steps include: 1) Preparation of palladium nanoparticles: 100 parts by weight of a reducing solvent, 3 to 10 parts by weight of a palladium salt and 5 to 32 parts by weight of a dispersant are weighed, all of the reducing solvent, the palladium salt and half of the dispersant are added to a reaction container in sequence, stirred evenly and heated to the reaction temperature for reaction, after reacting for 30 minutes, the remaining half of the dispersant is added dropwise, and the addition is completed within 1 hour, and the mass ratio of the dispersant to the palladium salt in the reaction system is controlled to be maintained at 1.5 to 6:1, and after the reaction is completed, stirring is continued and the mixture is naturally cooled to room temperature to obtain a mother liquor containing palladium nanoparticles; 2) filtering the mother liquor containing palladium nanoparticles, then adding deionized water and a fluorinated surfactant, stirring and mixing until uniformly mixed to obtain the palladium-based high-efficiency catalyst; In step 2), the weight percentage content of pure water in the palladium-based high-efficiency catalyst is 80% to 98%, and the weight percentage content of the fluorine-containing surfactant is 0.1% to 2%; In step 1), the reducing solvent is a mixed composite solvent of ethyl lactate and triethylene glycol; The mass ratio of ethyl lactate to triethylene glycol in the mixed composite solvent of ethyl lactate and triethylene glycol is 100:25-35; The palladium salt is a mixed composite palladium salt of palladium acetate and tetraammine palladium nitrate; The mass ratio of palladium acetate to palladium tetraamine nitrate in the mixed composite palladium salt of palladium acetate and palladium tetraamine nitrate is 1:0.1-0.
15.
2. The method for preparing a palladium-based high-efficiency catalyst according to claim 1, wherein During the preparation of the palladium nanoparticles, the stirring is uniform at a stirring temperature of 40 to 50°C, a stirring speed of 400 to 800 rpm, and a stirring time of 30 to 60 min; during the reaction, the reaction temperature is 95 to 125°C, the stirring speed is 400 to 800 rpm, and the reaction time is 1.5 to 2.5 h.
3. The method for preparing a palladium-based high-efficiency catalyst according to claim 1, wherein The dispersant is any one or more of Solsperse-3000, Solsperse-9000, Solsperse-24000, Solsperse-46000 and Solsperse-20000.
4. The method for preparing a palladium-based high-efficiency catalyst according to claim 1, wherein The surfactant is any one or more of perfluoro terminal carboxylates, perfluoroalkyl ethanesulfonates, perfluorooctyl methyl sulfates, perfluoroalkyl ether phosphates, perfluoropolyether carboxylates, fluorinated alkylamine quaternary ammonium salts, fluorinated alkyl amido quaternary ammonium salts, fluoroalkyl ammonium salts, carboxy betaine, sulfonate betaine, sulfate betaine, fluoroalkyl polyoxyethylene ether alcohol, fluorinated alkyl sulfonamide alcohol, fluorinated alkyl benzene and fluorinated alkane.
5. A palladium-based high-efficiency catalyst, characterized in that: The catalyst is prepared by the method for preparing a palladium-based high-efficiency catalyst as described in any one of claims 1 to 4.
6. Use of the palladium-based high-efficiency catalyst as claimed in claim 5 in chemical copper plating.
Citation Information
Patent Citations
Flexible conductive film, and preparation method and application thereof
CN111446453A
Metallic nanoparticle, manufacturing method of the same, and metallic printing ink composition containing the same
CN102205423A
Simple preparation method of palladium-based catalyst and palladium-based catalyst prepared by using same
CN103111292A